The Influence of Transformational Leadership Style, Work Environment, and Organizational Culture on Employee Performance at the Head Office of PT Bank BCA Syariah - Mikio Alif Hardi Ariyanto; Acep Samsudin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
This study aims to analyze the influence of transformational leadership style, work environment, and organizational culture on employee performance. The object of this research is the Head Office of PT. Bank BCA Syariah, located in East Jakarta. The population consists of employees from the Head Office, with a total sample of 80 respondents. This research employs an associative method with a quantitative approach. Data were collected through questionnaires and analyzed using multiple linear regression. The results indicate that, simultaneously, transformational leadership style, work environment, and organizational culture have a positive and significant effect on employee performance. Partially, the transformational leadership style does not have a significant effect on employee performance. The work environment has a significant effect, particularly in aspects such as lighting and available facilities, which support employee productivity. Organizational culture also shows a significant influence on employee performance, as it shapes shared values, beliefs, and behaviors that guide actions within the organization. This study provides practical implications for companies in designing human resource management strategies to improve employee performance.